Przekłady literatury serbskiej w Polsce w latach 2007—2013 - Małczak, Leszek (Przekłady Literatur Słowiańskich, 2014)
Translations of Serbian literature in the period from 2007 to 2013 There were translated about thirty books of Serbian literature in the period from 2007 to 2013, most of them were books of poetry. There were little number of translations in the literary magazines and journals. The number of translations is quite big but the reception of Serbian literature and culture was weak. The wars which accompanied the decay of the Second Yugoslavia has had big negative influence on the reception of Serbian literature and culture. Nowadays, after the fall of communism, literary contacts depend on initiative of individuals, the institution of translation literature has gone through the process of privatization. Key words: translation literature, Serbian literature in Poland, reception.